A structured ZSM-5 molecular sieve and its synthesis method and application

By generating secondary structure alkali liquid in the reaction between ZSM-5 molecular sieve and alkali liquid, and hydrothermal reaction with the slurry of silicon and aluminum sources, the problems of high cost, long time and insufficient regularity of ZSM-5 molecular sieve were successfully solved, and efficient and environmentally friendly regular ZSM-5 molecular sieve synthesis was achieved, which significantly improved its performance in the catalytic field.

CN119461410BActive Publication Date: 2025-04-25SHANDONG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510042295.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In the prior art, the cost of synthesizing ZSM-5 molecular sieve is high, the time is long, and the regularity needs to be improved.

Method used

By mixing the ZSM-5 molecular sieve with the alkali solution for reaction, the ZSM-5 secondary structure alkali solution was obtained, and added to the slurry of the silicon source and the aluminum source, and hydrothermal reaction was carried out to achieve the synthesis of the regular ZSM-5 molecular sieve.

Benefits of technology

The synthesis of ZSM-5 molecular sieve with high crystallinity and uniform morphology is achieved, avoiding the use of a large number of organic templates and ZSM-5 seeds, significantly reducing the synthesis cost and time, and showing excellent reaction performance in the catalytic field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461410B_ABST
    Figure CN119461410B_ABST
Patent Text Reader

Abstract

The present invention discloses a regular ZSM-5 molecular sieve and its synthesis method and application, and belongs to the field of catalyst and its synthesis technology. ZSM-5 molecular sieve is mixed with alkali liquor, centrifuged after reacting for 2-6h at 25-200 ℃, and ZSM-5 secondary structure alkali liquor is obtained; Aluminum source acid solution is added to silicon source alkali solution, gel is obtained and slurry is obtained by beating; ZSM-5 secondary structure alkali liquor is added to the above slurry and mixed, transferred to a hydrothermal reactor, and dynamic or static crystallization is carried out, and after crystallization, washing, drying and roasting are obtained to obtain regular ZSM-5 molecular sieve. The present invention is mild in conditions when preparing ZSM-5 secondary structure, and the alkaline solution used can be further applied to ZSM-5 molecular sieve synthesis gel system, maximizes the use of alkaline solution, ZSM-5 secondary structure is complete and guides ZSM-5 crystallization nucleation ability is strong, and the secondary structure can increase the openness of pore structure, widen the scope of use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and synthesis thereof, and specifically relates to a regular ZSM-5 molecular sieve and a synthesis method and application thereof. Background Art

[0002] ZSM-5 molecular sieve has MFI topological structure, and its Si / Al ratio can be adjusted in a wide range. All-silicon MFI molecular sieve (Silicalite-1) can also be prepared. It is this characteristic that makes the type, strength and distribution of its solid acid freely adjustable. The three-dimensional ten-membered ring channel structure of ZSM-5 molecular sieve makes it have certain characteristics in the fields of catalysis, adsorption, separation, etc. It also has certain shape selectivity. For example, it can be used for catalytic cracking of light gasoline and catalytic cracking to produce more propylene additives in the field of petrochemicals and fine chemicals. It can be used for nitrogen oxides (NO x ) and can be used for the rapid adsorption of volatile organic compounds (VOCs) instead of activated carbon, etc.

[0003] As a molecular sieve for large-scale industrial applications, the synthesis cost of ZSM-5 has attracted attention. It is mainly divided into synthesis under the guidance of organic templates, synthesis under the guidance of seeds, synthesis under filling with ethanol, etc., and mixed use of various methods. Among the many synthesis methods, the use of organic structure directing agents (such as tetrapropylammonium hydroxide, tetrapropylammonium bromide, tetraethylammonium hydroxide, n-butylamine, etc.) not only increases the preparation cost of molecular sieves but also causes certain pollution to the environment. These factors are not conducive to its long-term development. In order to solve the problems of the ZSM-5 molecular sieve series, many patents or academic reports have disclosed the synthesis of ZSM-5 molecular sieves without organic templates and have been successful. Compared with the synthesis process under organic structure directing agents, the organic template-free method is simpler and more environmentally friendly. For example, ZSM-5 molecular sieves were successfully synthesized under the guidance of seeds (patents CN 114394605A, CN102001679A, CN102502696A), but the molecular sieves obtained have irregular morphology or the amount of seeds used is about 10wt% of the mass of SiO2 in the system. The large amount used increases the synthesis cost. Dr. Liu Chunyan's doctoral thesis "Particle Size Control in Hydrothermal Synthesis of ZSM-5 Zeolite" (Dalian University of Technology, 2014) explored the synthesis of ZSM-5 using ZSM-5 and Silicalate-1 of various morphologies and sizes as seeds, and studied the synthesis of ZSM-5 molecular sieves using the supernatant collected after 50 nm nano ZSM-5 was treated with alkaline solution at high temperature for a long time (170 °C, 6h) as a directing agent. However, it takes about 40 h for complete crystallization, and there are problems such as long crystallization time and high alkali treatment temperature, which are not conducive to industrial transformation, and the regularity of the synthesized molecular sieve needs to be improved. Summary of the invention

[0004] In view of the problems in the prior art of synthesizing ZSM-5 molecular sieves, such as high cost, long time and the need to improve regularity, the present invention provides a regular ZSM-5 molecular sieve and a synthesis method and application thereof, thereby obtaining a ZSM-5 molecular sieve with high crystallinity and uniform morphology, avoiding the use of a large number of organic templates and ZSM-5 seed crystals, and exhibiting excellent reaction performance in the fields of catalytic hydrocarbon production, catalytic cracking and selective catalytic reduction of nitrogen oxides.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for synthesizing a structured ZSM-5 molecular sieve comprises the following steps:

[0007] (1) Mixing ZSM-5 molecular sieve with alkali solution, reacting at 25-200°C for 2-6 hours, and then centrifuging to obtain ZSM-5 secondary structure alkali solution;

[0008] (2) adding the aluminum source acid solution to the silicon source alkaline solution to obtain a gel and beating the gel to obtain a slurry;

[0009] (3) Adding the ZSM-5 secondary structure alkali solution in step (1) to the slurry in step (2), the mixture is transferred to a hydrothermal reactor for dynamic or static crystallization, and after the crystallization is completed, washing, drying, and calcining to obtain a regular ZSM-5 molecular sieve.

[0010] Furthermore, in step (1), the concentration of the alkali solution is 0.2-5 mol / L, the mass ratio of the alkali solution to the ZSM-5 molecular sieve is 1:1-50, the alkali solution is one of potassium hydroxide, cesium hydroxide, sodium hydroxide, ammonia and an organic alkali solution; and the organic base is one or more of tetramethylammonium hydroxide, ethylenediamine and triethylamine.

[0011] Furthermore, in step (2), the silicon source is one or more of water glass, fumed silica, silica sol, and white carbon black, and the aluminum source is one or more of aluminum sulfate, sodium aluminate, pseudo-boehmite, and boehmite.

[0012] Furthermore, the molar ratio of the silicon source, aluminum source, alkali, acid and water in the slurry of step (2) is 1:0.005-0.05:0.2-0.7:0.1-0.4:10-60, wherein the silicon source, aluminum source and alkali are calculated as oxides SiO2:Al2O3:M2O, and the acid is calculated as acid molecules; the acid is one or more of hydrochloric acid, nitric acid, acetic acid and sulfuric acid; and the alkali is one or more of calcium carbonate, magnesium carbonate, sodium hydroxide, potassium hydroxide and lithium hydroxide.

[0013] Furthermore, in step (3), the dynamic crystallization speed is 10-50 rpm, the crystallization temperature is 100-210°C, the crystallization time is 15-60 h, the drying temperature is 50-120°C, the calcination temperature is 450-850°C, and the time is 4-10 h.

[0014] In the present invention, the regular ZSM-5 molecular sieve synthesized by the above method has a specific surface area of ​​300-510 m 2 / g, micropore volume is 0.20~0.42 mL / g, mesopore volume is 0.10~0.27 mL / g, grain size is 30~300 nm, and silicon-aluminum ratio is 25~200.

[0015] In the present invention, the structured ZSM-5 molecular sieve is used to catalyze methanol to produce light olefins in the process of converting methanol to olefins.

[0016] In the present invention, the structured ZSM-5 molecular sieve is used to catalyze the nitrogen oxide reduction reaction using ammonia as a reducing agent.

[0017] In the present invention, the structured ZSM-5 molecular sieve is used to catalyze petroleum hydrocarbons to produce light olefins in the catalytic cracking of petroleum to olefins reaction.

[0018] Beneficial effects:

[0019] (1) The method for synthesizing the regular ZSM-5 molecular sieve of the present invention does not require the use of a template, has a short crystallization time, a regular and highly consistent morphology, and has a high yield (more than 90%), a high crystallinity (more than 90%), and excellent acid properties;

[0020] (2) The present invention uses mild conditions when preparing the ZSM-5 secondary structure, and the alkaline solution used can be further applied to the ZSM-5 molecular sieve synthesis gel system to maximize the use of the alkaline solution. The ZSM-5 secondary structure is complete and has a strong ability to guide the crystallization nucleation of ZSM-5. The secondary structure can increase the openness of the pore structure and broaden the scope of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the infrared spectrum of the alkali solution of the secondary structure of ZSM-5 in Example 1;

[0022] Figure 2 X-ray diffraction patterns of ZSM-5-1, ZSM-5-CA, ZSM-5-3 and ZSM-5-5;

[0023] Figure 3 This is the SEM image of ZSM-5-1 prepared in Example 1;

[0024] Figure 4 This is the SEM image of ZSM-5-S prepared in Comparative Example 1;

[0025] Figure 5 This is the SEM image of commercial ZSM-5-C;

[0026] Figure 6 Methanol to olefins (MTO) performance diagram of the catalyst;

[0027] Figure 7 This is the denitrification performance diagram of the catalyst. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the following examples, the molecular sieve is a commercially available molecular sieve ZSM-5-C, with a silicon-aluminum ratio of 30, a relative crystallinity of 95%, and a specific surface area of ​​370 m 2 / g, micropore volume is 0.31 mL / g, mesopore volume is 0.13 mL / g, and grain size is 200-500 nm; its SEM image is shown in Figure 5 shown.

[0030] Main analytical test methods

[0031] (1) ZSM-5 crystallinity: X-ray diffraction method, the sum of the peak areas of the five characteristic diffraction peaks in the 2θ range of 22.5~25° of the XRD spectrum of the sample and the standard sample is measured respectively, and the percentage value is the content of ZSM-5; the standard sample is a high-quality ZSM-5 molecular sieve produced by Nankai, and its crystallinity is set at 98%;

[0032] (2) Elemental composition and silicon-aluminum ratio: XRF fluorescence analysis;

[0033] (3) Morphology: SEM analysis;

[0034] (4) Specific surface area and pore volume: nitrogen adsorption method.

[0035] Example 1

[0036] (1) Dissolve 0.13 g potassium hydroxide in 3 mL water, add 0.3 g ZSM-5-C molecular sieve, treat at 120 °C for 2 h, and centrifuge to obtain a solid ZSM-5-CA (the X-ray diffraction pattern of ZSM-5-CA is shown in Figure 2As shown in FIG. 1 ), a supernatant containing a ZSM-5 secondary structure (ZSM-5 secondary structure alkali solution) is obtained at the same time. The infrared spectrum of the ZSM-5 secondary structure alkali solution is shown in FIG. Figure 1 As shown in the infrared spectrum, at 620 cm -1 The obvious absorption peak at directly proves the existence of the secondary structure of ZSM-5;

[0037] (2) 1.834 g aluminum sulfate was added to 13.5 g hydrochloric acid solution (2.44 mol / L) to dissolve, and then slowly added dropwise to 23.2 g water glass solution (SiO2 content: 22.08 wt%, Na2O content: 6.33 wt%) to form a mixed gel and fully slurried to obtain a slurry. The ratio of each material in the slurry was: SiO2 / Al2O3 = 31, Na2O / SiO2 = 0.3; HCl / Na2O = 0.82; H2O / SiO2 = 21;

[0038] (3) The ZSM-5 secondary structure alkali solution in step (1) is added to the slurry in step (2), mixed and slurried, and then transferred to a hydrothermal reactor for crystallization at 170°C for 20 h. The crystallized product is filtered, washed, dried at 60°C, and then calcined at 580°C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-1), whose X-ray diffraction pattern is as shown below: Figure 2 As shown in the SEM images Figure 3 As shown, ZSM-5-1 is composed of regular primary grains with a size of about 200 nm;

[0039] The results of analysis and testing show that the relative crystallinity of ZSM-5-1 is 92% and the specific surface area is 405 m 2 / g, the micropore volume is 0.33 mL / g, the mesopore volume is 0.12 mL / g, the grain size is 110 nm, and the silicon-aluminum ratio is 30.

[0040] Example 2

[0041] (1) Dissolve 0.19 g of cesium hydroxide in 3.5 mL of water, add 0.36 g of ZSM-5-C molecular sieve, treat at 140 °C for 4 h, and then centrifuge to obtain ZSM-5 secondary structure alkali solution;

[0042] (2) 1.834 g aluminum sulfate was added to 13.5 g sulfuric acid solution (1.42 mol / L) to dissolve, and then slowly added to the silicon source solution (5.2 g white carbon black (SiO2 content is 97 wt%) dissolved in 17.6 g, 2.6 mol / L sodium hydroxide solution) to form a gel and slurry. The ratio (molar ratio) of each material in the slurry is: SiO2 / Al2O3=31; Na2O / SiO2=0.3; H2SO4 / Na2O=0.77; H2O / SiO2=22;

[0043] (3) adding the ZSM-5 secondary structure alkali solution in step (1) to the slurry in step (2), mixing and slurrying, transferring to a hydrothermal reactor, crystallizing at 170°C for 22 h, filtering, washing, and drying at 60°C after the crystallization, and then calcining at 550°C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-2);

[0044] The results of analysis and testing show that the relative crystallinity of ZSM-5-2 is 91% and the specific surface area is 398 m 2 / g, the micropore volume is 0.31 mL / g, the mesopore volume is 0.11 mL / g, the grain size is about 120 nm, and the silicon-aluminum ratio is 30.

[0045] Example 3

[0046] (1) Dissolve 0.19 g of sodium hydroxide in 3.1 mL of water, add 0.4 g of ZSM-5-C molecular sieve, treat at 150 °C for 4 h, and then centrifuge to obtain ZSM-5 secondary structure alkali solution;

[0047] (2) 0.28 g of boehmite (Al2O3 content of 95 wt%) was added to 13.5 g of hydrochloric acid solution (2.74 mol / L) to dissolve, and then slowly added to the silicon source solution (5.2 g of white carbon black (SiO2 content of 97 wt%) was dissolved in 17.6 g of 2.5 mol / L sodium hydroxide solution) to form a gel and slurry. The ratio (molar ratio) of each material in the slurry was: SiO2 / Al2O3 = 32; Na2O / SiO2 = 0.29; HCl / Na2O = 1.52; H2O / SiO2 = 21;

[0048] (3) The ZSM-5 secondary structure alkali solution in step (1) is added to the slurry in step (2), mixed and slurried, and then transferred to a hydrothermal reactor for crystallization at 170°C for 20 h. The crystallized product is filtered, washed, dried at 60°C, and then calcined at 650°C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-3), whose X-ray diffraction pattern is shown in FIG. Figure 2 As shown;

[0049] The results of analysis and testing show that the relative crystallinity of ZSM-5-3 is 90% and the specific surface area is 412 m 2 / g, the micropore volume is 0.30 mL / g, the mesopore volume is 0.15 mL / g, the grain size is about 100 nm, and the silicon-aluminum ratio is 32.

[0050] Example 4

[0051] (1) Disperse 0.73 g of ammonia water into 4.6 mL of water, add 0.5 g of ZSM-5-C molecular sieve, treat at 130 °C for 5 h, and then centrifuge to obtain ZSM-5 secondary structure alkali solution;

[0052] (2) 0.39 g of pseudo-boehmite (Al2O3 content of 70 wt%) was added to 14.5 g of sulfuric acid solution (1.31 mol / L) to dissolve, and then slowly added to a silicon source solution (5.2 g of fuming silica gel (SiO2 content of 98 wt%) dissolved in 17.6 g of 2.5 mol / L potassium hydroxide solution) to form a gel and slurry. The ratio (molar ratio) of each material in the slurry was: SiO2 / Al2O3 = 31; Na2O / SiO2 = 0.26; H2SO4 / Na2O = 0.78; H2O / SiO2 = 23;

[0053] (3) adding the ZSM-5 secondary structure alkali solution in step (1) to the slurry in step (2), mixing and slurrying, transferring to a hydrothermal reactor, dynamically crystallizing at 170°C for 20 h, filtering, washing, and drying at 60°C after the crystallization, and then calcining at 550°C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-4);

[0054] The results of analysis and testing show that the relative crystallinity of ZSM-5-4 is 89% and the specific surface area is 389 m 2 / g, the micropore volume is 0.29 mL / g, the mesopore volume is 0.16 mL / g, the grain size is about 130 nm, and the silicon-aluminum ratio is 31.

[0055] Example 5

[0056] (1) Disperse 0.29 g of ethylenediamine in 3.1 mL of water, add 0.49 g of ZSM-5-C molecular sieve, treat at 150 °C for 4 h, and then centrifuge to obtain ZSM-5 secondary structure alkali solution;

[0057] (2) 0.395 g aluminum sulfate was added to 14.2 g hydrochloric acid solution (1.32 mol / L) to dissolve, and then slowly added to 23.2 g water glass (SiO2 content: 22.08 wt%, Na2O content: 6.33 wt%) to form a gel, and the slurry was prepared. The ratio (molar ratio) of each material in the slurry was: SiO2 / Al2O3=144; Na2O / SiO2=0.28; H2SO4 / Na2O=0.71; H2O / SiO2=21;

[0058] (3) The ZSM-5 secondary structure alkali solution in step (1) is added to the slurry in step (2), mixed and slurried, and then transferred to a hydrothermal reactor for crystallization at 170°C for 21 h. The crystallized product is filtered, washed, dried at 60°C, and then calcined at 550°C for 6 h to obtain a regular ZSM-5 molecular sieve (ZSM-5-5), whose X-ray diffraction pattern is shown in FIG. Figure 2 As shown;

[0059] The results of analysis and testing show that the relative crystallinity of ZSM-5-5 is 93% and the specific surface area is 425 m 2 / g, the micropore volume is 0.35 mL / g, the mesopore volume is 0.18 mL / g, the grain size is about 120 nm, and the silicon-aluminum ratio is 140.

[0060] Comparative Example 1

[0061] Unlike Example 1, Comparative Example 1 does not include step (1), and uses 10 wt% ZSM-5-C seed crystals (calculated as SiO2) to replace the ZSM-5 secondary structure alkali solution in Example 1. The remaining operations are the same as those in Example 1 to prepare a ZSM-5 molecular sieve (ZSM-5-S). Its SEM image is shown in FIG. Figure 4 As shown in Figure 2, ZSM-5-S is composed of primary grains with a size of about 210 nm. The primary grains are rough and lack regularity, which is consistent with the Figure 3 Completely different;

[0062] The results of analysis and testing show that the relative crystallinity of ZSM-5-S is 88% and the specific surface area is 395 m 2 / g, the micropore volume is 0.28 mL / g, the mesopore volume is 0.11 mL / g, the grain size is about 140 nm, and the silicon-aluminum ratio is 30.

[0063] Comparative Example 2

[0064] (1) 0.395 g of aluminum sulfate was added dropwise to 23.2 g of water glass (SiO2 content: 22.08 wt%, Na2O content: 6.33 wt%) to form a gel and then slurried into a slurry. The ratio (molar ratio) of each material in the slurry was: SiO2 / Al2O3=144, Na2O / SiO2=0.3, H2O / SiO2=21;

[0065] (2) 10 wt% ZSM-5-C seed crystals (calculated as SiO2) were added to the slurry of step (1), and the mixture was further mixed and slurried, and then transferred to a synthesis reactor and crystallized at 170°C for 48 h. The crystallized product was filtered, washed, dried at 60°C, and calcined at 550°C for 6 h to obtain ZSM-5 molecular sieve (ZSM-5-S2).

[0066] The results of analysis and testing show that the relative crystallinity of ZSM-5-S2 is 87% and the specific surface area is 398 m 2 / g, the micropore volume is 0.23 mL / g, the mesopore volume is 0.10 mL / g, and the silicon-aluminum ratio is 140.

[0067] Comparative Example 3

[0068] (1) Disperse 104 g of silica sol in 10 g of deionized water, then add 23.63 g of NaOH solid and stir at room temperature for sufficient hydrolysis for 1 h to obtain solution A; disperse 2.3 g of Al2O3 powder in 100 g of deionized water, then dropwise add 26.06 g of concentrated sulfuric acid and stir for 1 h to obtain solution B;

[0069] (2) Liquid B was slowly added dropwise to liquid A, and 3.2 wt% of ZSM-5-C seed crystals were added and stirred to obtain a gel. The gel composition was: SiO2 / Al2O3=30, Na2O / SiO2=0.06, H2O / SiO2=26, H2SO4 / Na2O=0.88; the mixture was transferred to a synthesis reactor, sealed, and crystallized at 170°C for about 20 h. The crystallized product was filtered, washed, dried at 110°C, and then calcined at 570°C for 6 h to obtain ZSM-5 molecular sieve (ZSM-5-S3);

[0070] The results of analysis and testing show that the relative crystallinity of ZSM-5-S3 is 90% and the specific surface area is 401 m 2 / g, the micropore volume is 0.31 mL / g, the mesopore volume is 0.10 mL / g, the grain size is about 150 nm, and the silicon-aluminum ratio is 30.

[0071] Comparative Example 4

[0072] (1) Disperse 0.3 g of ZSM-5 molecular sieve with a diameter of 50 nm into 1.5 mL of alkaline solution (0.27 mol / L), treat at 170 °C for 6 h, and then centrifuge to obtain an alkaline solution of ZSM-5 secondary structural units;

[0073] (2) 1.834 g aluminum sulfate was added to 13.5 g sulfuric acid solution (1.22 mol / L) to dissolve, and then slowly added dropwise to 23.2 g water glass (SiO2 content: 22.08 wt%, Na2O content: 6.33 wt%) to form a gel and slurry was formed. The ratio (molar ratio) of each material in the slurry was: SiO2 / Al2O3=31, Na2O / SiO2=0.3, H2SO4 / Na2O=0.41, H2O / SiO2=21;

[0074] (3) The alkaline solution of the ZSM-5 secondary structural unit prepared in step (1) is added to the slurry in step (2), and the mixture is further mixed and slurried, and crystallized at 170°C for 40 h. The crystallized product is filtered, washed, dried at 80°C, and then calcined at 560°C for 6 h to obtain a ZSM-5 molecular sieve (ZSM-5-L).

[0075] The results of analysis and testing show that the relative crystallinity of ZSM-5-L is 89% and the specific surface area is 402 m 2 / g, the micropore volume is 0.31 mL / g, the mesopore volume is 0.11 mL / g, the grain size is about 190 nm, and the silicon-aluminum ratio is 30.

[0076] The X-ray diffraction patterns of ZSM-5-1 of Example 1, the remaining solid ZSM-5-CA after extracting the secondary structure of ZSM-5, ZSM-5-3 of Example 3, and ZSM-5-5 of Example 5 are as follows: Figure 2 As shown by Figure 2 It can be seen that the pure phase ZSM-5 molecular sieve was successfully synthesized in the embodiment, and the MFI topological structure of the commercial ZSM-5 molecular sieve was still maintained after alkali treatment.

[0077] Application Example 1

[0078] The ZSM-5-5 prepared in Example 5 and the ZSM-5-S2 prepared in Comparative Example 2 were stirred in a 1 mol / L NH4Cl solution at 80°C for 4 h, washed, dried and calcined to obtain proton-type H-ZSM-5-5 and H-ZSM-5-S2 catalysts, which were used to catalyze the methanol to light olefins (MTO) reaction. The reaction conditions were as follows:

[0079] 200 mg of H-ZSM-5-5 catalyst was placed in a quartz tube with an inner diameter of 8 mm and heated at 30 mL min -1 The activation was carried out at 500 °C for 1 h under N2 flow rate. After activation, the temperature dropped to 400 °C and then the injection was started. The feeding rate of methanol was 0.126 mL·h -1 The carrier gas was N2 at a flow rate of 30 mL min -1 The mass space velocity (WHSV) under this condition is 1.0 h -1 The product analysis was completed by gas chromatography, and its catalytic performance (methanol conversion rate and propanol selectivity) is shown in the figure Figure 6 As shown, it is illustrated that the H-ZSM-5-5 prepared by the ZSM-5-5 prepared by the present invention exhibits better stability and propylene selectivity than the comparative H-ZSM-5-S2.

[0080] Application Example 2

[0081] The prepared ZSM-5-1, ZSM-5-S, ZSM-5-C and ZSM-5-CA were stirred in 1 mol / L NH4Cl solution at 80°C for 4 h, washed, dried and calcined to obtain proton-type H-ZSM-5-1, H-ZSM-5-S, H-ZSM-5-C and H-ZSM-5-CA; then 0.23 g of copper nitrate trihydrate and 4 g of deionized water were mixed with 1 g of H-ZSM-5-1, H-ZSM-5-S, H-ZSM-5-C or H-ZSM-5-CA molecular sieves, respectively, stirred at 80°C for 6 h, filtered, washed and dried at 80°C, and the dried products were calcined at 550°C for 6 h. h, the target products obtained are calcined Cu-ZSM-5-1, Cu-ZSM-5-S, Cu-ZSM-5-C and Cu-ZSM-5-CA, whose structures are consistent with ZSM-5-1, ZSM-5-S, ZSM-5-C and ZSM-5-CA. The above catalysts (Cu-ZSM-5-1, Cu-ZSM-5-S, Cu-ZSM-5-C and Cu-ZSM-5-CA) are applied to the selective catalytic reduction reaction of nitrogen oxides (NH3-SCR) with ammonia as a reducing agent, and the reaction conditions are as follows:

[0082] 100 mg of the catalyst was placed in a quartz tube with an inner diameter of 8 mm, in a mixture of 500 ppm NO, 500 ppm NH3, 5% O2, and Ar as the balance gas at a flow rate of 100 mL min -1 , mass space velocity (WHSV) is 4,800 h -1 The test temperature range is 100-600 o C, exhaust gas analysis is completed by flue gas analyzer. The catalyst has a wide temperature window and N2 selectivity reaches more than 95% within the test temperature range. The denitrification performance diagram is as follows Figure 7 As shown, Cu-ZSM-5-1 prepared from the ZSM-5-1 of the present invention performs better than the comparative Cu-ZSM-5-S, Cu-ZSM-5-C and Cu-ZSM-5-CA.

[0083] Application Example 3

[0084] By adopting the above method, ZSM-5-1 prepared in Example 1, ZSM-5-S prepared in Comparative Example 1, ZSM-5-S3 prepared in Comparative Example 3, and ZSM-5-L prepared in Comparative Example 4 were respectively prepared into H-ZSM-5-1, H-ZSM-5-S, H-ZSM-5-S3 and H-ZSM-5-L catalysts, which were applied to the catalytic cracking reaction of naphtha, and the reaction conditions were as follows:

[0085] 2 g of the catalyst was placed in a quartz tube with an inner diameter of 8 mm and heated at 30 mL min -1 The activation was carried out at 600 °C for 1 h under N2 flow rate. After activation, the temperature dropped to 550 °C and the injection was started. The feed amount of naphtha was 0.7 g, the feed rate was 0.7 g / min, and the carrier gas was N2 at a flow rate of 30 mL·min -1 The product analysis was completed by gas chromatography. The micro-reaction activity (MAT) data of the catalyst are shown in Table 1. As can be seen from Table 1, in terms of naphtha conversion and diene (ethylene and propylene) selectivity, H-ZSM-5-1 prepared by ZSM-5-1 of the present invention is superior to the comparative H-ZSM-5-S, H-ZSM-5-3 and H-ZSM-5-L.

[0086] Table 1 Micro-reaction activity (MAT) data of catalysts

[0087] .

Claims

1. A method for synthesizing a structured ZSM-5 molecular sieve, characterized in that: The following steps are involved: (1) Mixing ZSM-5 molecular sieve with alkali solution, reacting at 120-150°C for 2-5 hours, and then centrifuging to obtain ZSM-5 secondary structure alkali solution; (2) adding the aluminum source acid solution to the silicon source alkaline solution to obtain a gel and beating the gel to obtain a slurry; (3) adding the ZSM-5 secondary structure alkali solution in step (1) to the slurry in step (2), transferring the mixture to a hydrothermal reactor for dynamic or static crystallization, and washing, drying, and calcining after the crystallization to obtain a regular ZSM-5 molecular sieve; The concentration of the alkali solution in step (1) is 0.2-5 mol / L; In step (3), the dynamic crystallization speed is 10-50 rpm, the crystallization temperature is 100-210°C, the crystallization time is 15-22 h, the drying temperature is 50-120°C, the calcination temperature is 450-850°C, and the time is 4-10 h.

2. The method for synthesizing a structured ZSM-5 molecular sieve according to claim 1, characterized in that: In step (1), the mass ratio of the alkali solution to the ZSM-5 molecular sieve is 1:1-50, the alkali solution is one of potassium hydroxide, cesium hydroxide, sodium hydroxide, ammonia and an organic alkali solution; the organic base is one or more of tetramethylammonium hydroxide, ethylenediamine and triethylamine.

3. The method for synthesizing a structured ZSM-5 molecular sieve according to claim 1, characterized in that: In step (2), the silicon source is one or more of water glass, fumed silica, silica sol, and white carbon black, and the aluminum source is one or more of aluminum sulfate, sodium aluminate, pseudo-boehmite, and boehmite.

4. The method for synthesizing a structured ZSM-5 molecular sieve according to claim 1, characterized in that: The molar ratio of the silicon source, aluminum source, alkali, acid and water in the slurry of step (2) is 1:0.005-0.05:0.2-0.7:0.1-0.4:10-60, wherein the silicon source, aluminum source and alkali are calculated as oxides SiO2:Al2O3:M2O, and the acid is calculated as acid molecules; the acid is one or more of hydrochloric acid, nitric acid, acetic acid and sulfuric acid; and the alkali is one or more of calcium carbonate, magnesium carbonate, sodium hydroxide, potassium hydroxide and lithium hydroxide.

5. A regular ZSM-5 molecular sieve synthesized by the method according to any one of claims 1 to 4, characterized in that: The specific surface area of ​​the structured ZSM-5 molecular sieve is 300-510 m 2 / g, micropore volume is 0.20~0.42 mL / g, mesopore volume is 0.10~0.27 mL / g, grain size is 30~300 nm, and Si-Al ratio is 25~180.

6. An application of the structured ZSM-5 molecular sieve according to claim 5, characterized in that: In the methanol to olefins conversion process, methanol is catalyzed to produce light olefins.

7. An application of the structured ZSM-5 molecular sieve according to claim 5, characterized in that: Catalyzes the reduction of nitrogen oxides using ammonia as a reducing agent.

8. An application of the structured ZSM-5 molecular sieve according to claim 5, characterized in that: In the catalytic cracking of petroleum to olefins reaction, petroleum hydrocarbons are catalyzed to produce light olefins.

Citation Information

Patent Citations

  • Method for preparing molecular sieve ZSM-5

    CN102001679A

  • Synthetic method of ZSM-5 zeolites

    CN102502696A

  • Method for producing ethene and propylene by catalytic cracking

    CN102746889A

  • Nanometer ZSM-5 molecular sieve aggregate synthesis method

    CN109694087A

  • Method for synthesizing ZSM-5 molecular sieve without organic template agent

    CN116692895A